2019
DOI: 10.1038/s41598-019-42442-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of exogenous melatonin on clinical and pathological features of a human thyroglobulin-induced experimental autoimmune thyroiditis mouse model

Abstract: Melatonin (MLT) plays a significant role in both innate and adaptive immunity, and dysregulation of the MLT signature can modify autoimmune disease phenotypes. In this study, the influence of exogenous MLT administration on regulating autoimmune thyroiditis animal models was evaluated. An experimental autoimmune thyroiditis model was established in MLT-synthesizing (CBA) and MLT-deficient (C57BL/6) mice by immunization with human thyroidglobulin (TG), which features thyrotoxicosis, thyrocyte damage, and CD3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A third membrane-bound MTNbinding site, the MT3 receptor, was theorized as a biological target of MTN and was found to, in fact, act as the cytosolic enzyme, quinone reductase II (NQO2) 12 . Some authors have reported in their genetic study that the single-nucleotide polymorphism of MTN receptor type 1A, MTNR1A, coding the MT1 protein, was associated with a sensitivity to Graves' disease and thyroid autoantibody formation, which supports the impression, that MTN can influence the development of autoimmune thyroid disease in thyroidology 13,14 . The thyroid gland is characterized by a high level of oxidative stress, and the use of pro-oxidants can lead to miscellaneous damage and diseases of this delicate papillon gland.…”
mentioning
confidence: 78%
“…A third membrane-bound MTNbinding site, the MT3 receptor, was theorized as a biological target of MTN and was found to, in fact, act as the cytosolic enzyme, quinone reductase II (NQO2) 12 . Some authors have reported in their genetic study that the single-nucleotide polymorphism of MTN receptor type 1A, MTNR1A, coding the MT1 protein, was associated with a sensitivity to Graves' disease and thyroid autoantibody formation, which supports the impression, that MTN can influence the development of autoimmune thyroid disease in thyroidology 13,14 . The thyroid gland is characterized by a high level of oxidative stress, and the use of pro-oxidants can lead to miscellaneous damage and diseases of this delicate papillon gland.…”
mentioning
confidence: 78%
“…Those tissues were not collected for the KRT1 mRNA analysis in the current study, and the main source of elevated serum KRT1 in GD remains unclear. It is our future plan to gather mouse serum, skin, thyroid, and peripheral white blood cells at the same time, to quantify KRT1 transcripts of these tissues using the mouse thyroiditis model built by our laboratory, to elucidate the possible origin of elevated serum KRT1 stimulated by the TH [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental model of hypothyroidism, it has been demonstrated that melatonin could increase the level of thyroid hormones via regulating the neuroendocrine axis and upregulation of TSH, pointing out that exogenous melatonin differentially modulates the MT1 and MT2 receptor protein expression in the pituitary and thyroid gland (64). Additionally, it has been shown that melatonin can increase plasma thyroid hormone levels and enhance thyrocyte destruction and the T-cell proliferation capacity in the autoimmune thyroiditis mouse model (65). There is very limited evidence for the effects of supplemental melatonin on human thyroid function.…”
Section: Melatoninmentioning
confidence: 99%